2016
DOI: 10.1093/jxb/erv565
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a herbicide-metabolizing enzyme library inBeckmannia syzigachneto identify genes associated with metabolic resistance

Abstract: Non-target site resistance (NTSR) to herbicides is an increasing concern for weed control. Metabolic herbicide resistance is an important mechanism for NTSR. However, little is known about metabolic resistance at the genetic level. In this study, we have identified three fenoxaprop-P-ethyl-resistant American sloughgrass (Beckmannia syzigachne Steud.) populations, in which the molecular basis for NTSR remains unclear. To reveal the mechanisms of metabolic resistance, the genes likely to be involved in herbicide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
82
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 64 publications
7
82
0
1
Order By: Relevance
“…Consequently, many B. syzigachne populations have evolved resistance to fenoxaprop- P -ethyl, thereby rendering them as hard-to-control weeds (Pan et al, 2015b). In our previous studies, three fenoxaprop- P -ethyl-resistant B. syzigachne populations involving both TSR and NTSR were identified (Pan et al, 2015b), and our RNA-seq analysis detected structural changes and alterations in the transcriptional regulation of several genes encoding metabolizing enzymes (Pan et al, 2016). The RNA-seq analysis also showed that laccase gene expression was down-regulated in the three fenoxaprop- P -ethyl-resistant B. syzigachne populations.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…Consequently, many B. syzigachne populations have evolved resistance to fenoxaprop- P -ethyl, thereby rendering them as hard-to-control weeds (Pan et al, 2015b). In our previous studies, three fenoxaprop- P -ethyl-resistant B. syzigachne populations involving both TSR and NTSR were identified (Pan et al, 2015b), and our RNA-seq analysis detected structural changes and alterations in the transcriptional regulation of several genes encoding metabolizing enzymes (Pan et al, 2016). The RNA-seq analysis also showed that laccase gene expression was down-regulated in the three fenoxaprop- P -ethyl-resistant B. syzigachne populations.…”
Section: Introductionmentioning
confidence: 85%
“…Three fenoxaprop- P -ethyl-resistant B. syzigachne populations possessing both NTSR and TSR and one susceptible population (S) were used in this study (Pan et al, 2016). These populations were collected from the following locations: S from Feidong in Anhui Province, where fenoxaprop- P -ethyl was never applied; R1 from Xinlucun in Jiangsu Province with 10 years of fenoxaprop- P -ethyl use history; R2 from Lijiacun in Jiangsu Province, with 6 years of fenoxaprop- P -ethyl use; and R3 from Guocun in Jiangsu Province, with 5 years of fenoxaprop- P -ethyl use.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations